National Treasures - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
Every country has its national treasures. In this interview, Jackie Hughes of the World Vegetable Centre highlights the value of some food plant species, which she believes are treasures, but which have been neglected. These include plants such as amaranth, which can grow in marginal areas but which is also very nutritious. If more widely grown, these neglected crops could play a role in improving diets among the resource poor, and raising their income. They could also help to maintain farm production in the face of climate change.